DLC (diamond-like carbon) assisted stress release GaN / diamond integration method
By introducing a DLC auxiliary stress release layer into GaN/diamond integration, the thermal stress deformation problem between GaN and diamond is solved, the stability and yield of the integration are improved, and more efficient GaN/diamond module production is achieved.
Patent Information
- Application Number
- CN202510089480.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-21
AI Technical Summary
In the existing GaN/diamond integration technology, the lattice mismatch between GaN and diamond and the difference in thermal expansion coefficients lead to thermal stress deformation, affecting the stability and yield of the integration.
Using a DLC auxiliary stress release layer, by depositing a DLC film at room temperature on the Si substrate and growing a diamond heat dissipation layer at high temperature, the high thermal conductivity of DLC and adjustable thermal expansion coefficient assist stress release are used to reduce the interface thermal stress between GaN and diamond.
It effectively reduces the thermal stress deformation of GaN and diamond during heteroepitaxy growth, improves the stability and yield of integration, and enhances the application potential of GaN/diamond modules.
Smart Images

Figure CN119890032A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a GaN / diamond integration method, in particular to a DLC-assisted stress-release GaN / diamond integration method, belonging to the technical field of semiconductor power electronic devices. Background Art
[0002] The third generation of semiconductors represented by gallium nitride (GaN) are widely used in aerospace and 5G communications due to their wide bandgap, high thermal conductivity, excellent electron mobility and electron saturation drift velocity. The power chips made of GaN can withstand a maximum temperature of 600°C. They not only have high energy utilization efficiency but are also stable enough, and are expected to completely replace traditional Si-based power devices in the future.
[0003] With the progress of industrialization, the size of chips continues to shrink, and the performance requirements for power devices are also increasing. 3D integrated circuit (3DIC) technology is considered to be an important technology to cope with "Moore's Law". With the high-density power devices and chip bonding and packaging, heat dissipation is a process problem that needs to be solved urgently. GaN power devices produce certain losses when working, and this part of the power loss is gathered in the form of heat energy inside the device. In particular, the current GaN devices are mainly based on sapphire and Si substrates, and their thermal conductivity coefficients are 0.5W / cm·K and 1.5W / cm·K respectively, which causes heat to be concentrated on the GaN / substrate bonding surface, which has a great impact on the service life and service stability of GaN power devices.
[0004] In the prior art, the patent with publication number CN110838438A discloses a method for integrating diamond and gallium nitride. First, the gallium nitride epitaxial wafer and the temporary carrier are cleaned, and then the front faces of the two are temporarily bonded. After bonding, the substrate of the gallium nitride epitaxial wafer is removed, and then the gallium nitride epitaxial layer supported by the temporary carrier and the diamond substrate are placed in deionized water and bonded together, and then placed on a rotating table to dry, and the bonding surface forms a bonding layer, and then placed in a bonding machine for heating and pressurization, and finally the temporary carrier and adhesive material are removed. Diamond has extremely excellent thermal conductivity (22W / cm·K), and its application to assist GaN power device heat dissipation, that is, integrated GaN / diamond is a common method in the semiconductor field today. The integration of diamond and GaN power devices is mainly carried out from two aspects: one is the heat dissipation of the device layer on the top of GaN, which mainly uses diamond passivation heat dissipation technology; the other is the heat dissipation of the diamond substrate at the bottom of GaN, which mainly includes heteroepitaxial diamond at the bottom of GaN, heteroepitaxial GaN on the surface of diamond, and GaN and diamond bonding technology. However, due to the large lattice mismatch between GaN and diamond, the huge difference in thermal expansion coefficient, and the extremely high hardness of diamond, whether it is based on GaN or diamond, heteroepitaxial growth of the other will cause severe thermal stress deformation at the interface between GaN and diamond. At the same time, in heteroepitaxial growth, the growth environment of diamond requires extremely high temperature, which causes the GaN layer to have defects such as curling and fracture during the growth process or before the growth of the diamond layer, making it impossible for GaN and diamond to be well integrated.
[0005] In the field of heteroepitaxial diamond, the thickness of GaN is also an important factor affecting the growth of diamond and other buffer layers. When heteroepitaxial diamond layers are grown on GaN, the thickness of GaN will have a greater impact on the surface binding energy. Thick GaN has great application potential in the preparation of double-layer structures with GaN attached on both sides. At present, the calculation of the binding ability of GaN and diamond is usually shown as follows:
[0006] Among them, the binding energy The thickness of GaN It is proportional to the square of , so preparing thick GaN is an important means to heteroepitaxially grow high-quality diamond layers on GaN.
[0007] Diamond-Likecarbon (DLC) is an amorphous carbon with high hardness, ultra-low friction coefficient, excellent tribological properties, good biocompatibility, high optical transmittance, high thermal conductivity and high chemical inertness. DLC film is mainly composed of sp 3 Hybridized bonds and sp 2 Hybridized bond composition is a sp3 Hybridized carbon atoms are embedded in sp 2 The irregular network structure in the film. And its structural composition is closely related to most of the properties of DLC film, especially its thermal expansion coefficient depends on sp 3 Hybridized bonds and sp 2 The ratio of hybrid bonds, when sp 2 The higher the proportion of hybrid bonds, the greater the thermal expansion coefficient of DLC. By controlling the conditions during the preparation of DLC, the thermal expansion coefficient of the DLC layer can be controlled, and the stress release of GaN under high temperature conditions in GaN heteroepitaxial diamond can be assisted. More importantly: the preparation temperature of DLC is relatively low, and the industry can now prepare it at room temperature. At the same time, DLC has a strong adhesion ability and can be deposited on the surfaces of various metals, glass, ceramics and other materials. The roughness requirements for the samples are not high, and the preparation cost is low. It is an ideal material to assist GaN heteroepitaxial diamond. Summary of the invention
[0008] The object of the present invention is to provide a DLC-assisted stress-release GaN / diamond integration method in order to solve at least one of the above technical problems.
[0009] The present invention achieves the above-mentioned object through the following technical scheme: a DLC-assisted stress-released GaN / diamond integration method, comprising DLC-assisted stress-released GaN / diamond, wherein the DLC-assisted stress-released GaN / diamond is composed of a GaN layer, a Si substrate, a DLC-assisted stress-released layer, an AlN buffer layer and a diamond heat dissipation layer, wherein the GaN layer is located above the Si substrate, the DLC-assisted stress-released layer is located below the Si substrate, the AlN buffer layer is located above the GaN layer, and the diamond heat dissipation layer is located above the AlN buffer layer; The integrated approach includes the following steps: S1. Sample pretreatment: the Si-based GaN sample is ultrasonically cleaned with a cleaning solution and then dried with an Ar air gun. The GaN surface is protected and the Si substrate is ground and polished using a chemical mechanical polishing device, leaving a certain thickness of Si layer for the deposition of the DLC auxiliary layer. S2, preparing a DLC auxiliary layer, using an ion enhanced chemical vapor deposition method to deposit a DLC film on a Si substrate at room temperature, and then annealing the film; S3, preparing a GaN / diamond heat dissipation module, using a metal organic chemical vapor deposition method to grow an AlN buffer layer on the GaN surface, and then using a microwave plasma chemical vapor deposition method to grow high-quality heat dissipation diamond in a high-temperature growth manner; S4. Polish the Si / DLC auxiliary layer to obtain a complete GaN / diamond module.
[0010] As a further solution of the present invention: sample pretreatment specifically includes: S11, performing cleaning pretreatment on the surface of the Si-based GaN sample, placing the Si-based GaN sample in a cleaning solution prepared by 70 vol% concentrated sulfuric acid and 30 vol% hydrogen peroxide, heating it in a water bath under an ultrasonic cleaning device, raising the temperature from room temperature to 65°C at a rate of 5°C / min, ultrasonically cleaning it for 10 minutes, placing it in deionized water for ultrasonic cleaning for 10 seconds, and then taking it out; S12, using an Ar air gun to blow dry and set aside, protecting the GaN surface of the Si-based GaN sample with a chip protection film, grinding the Si substrate using a chemical mechanical polishing method, using 800, 1500, 2000, 3000 and 5000 mesh mechanical grinding discs, until 0.5 μm of the Si substrate remains and then polishing is performed; S13. The Si substrate is ground and polished using a polishing cloth and a polishing liquid. The polishing cloth is a Sat woven fabric polishing cloth, and the polishing liquid formula is: 40 vol% SiO2 and 60 vol% diamond; the particle size of SiO2 is 150 nm, the particle size of diamond powder is 50 nm, and the polishing speed is 3500 r / min.
[0011] As a further solution of the present invention: preparing the DLC auxiliary layer specifically includes: S21. Place the processed GaN sample Si side upwards, and place a layer of high-temperature resistant graphite felt at the bottom of the sample to prevent the chip protection film from burning or melting due to excessive temperature. Place the sample in the PECVD sample chamber. The gas introduced during the preparation is 99.99% pure Ar, and the carbon source is 99.99% pure CH4. The flow rate of CH4 is 20sccm, the flow rate of Ar is 10sccm, the base temperature is room temperature 27°C, the internal total pressure is 10-12Pa, the RF power is 170-175W, the sputtering current is 0.5-0.6A, and the deposition rate is 5nm / min. S22. Use a mechanical pump to perform preliminary vacuum extraction. After 30 minutes, the pressure in the sample chamber reaches 4 Pa. When the actual vacuum degree in the sample chamber reaches the preset pressure, use a molecular pump to extract high vacuum in the sample chamber until the vacuum degree in the sample chamber reaches 2×10 -3 Pa, and at the same time slowly heat the temperature in the sample chamber to maintain it at 45°C; S23, using Ar plasma to clean and activate the Si surface for 110 seconds; S24, the deposition is terminated after 4 hours, and Ar is refilled, and the sample chamber is waited to return to normal temperature and pressure, and the sample is taken out and washed with deionized water, and dried with Ar to obtain a 1200nm DLC auxiliary layer; S25. Place the Si-based GaN sample with the DLC auxiliary layer prepared in an atmosphere furnace and anneal it at 200° C. in a N2 atmosphere for 60 minutes.
[0012] As a further solution of the present invention: preparing the GaN / diamond heat dissipation module specifically includes: S31, facing the GaN surface of the annealed sample upwards, removing the chip protection film, and placing the sample on a high temperature resistant graphite felt in the MOCVD sample chamber; S32, NH3 as N source, TMAl as Al source, flow rates of 25000sccm and 240sccm respectively, growth temperature of 800℃, power of 1500W, growth pressure of 3×10 4 Pa; after 150 minutes of deposition, Ar is backfilled, and when the sample chamber returns to normal temperature and pressure, the sample with the AlN buffer layer deposited is taken out, and it is ultrasonically cleaned with anhydrous ethanol and deionized water for 10 minutes, and blown dry with an Ar air gun, and then placed on the graphite felt in the microwave chamber of the MPCVD for the final growth of the heat dissipation diamond layer; S33, use mechanical pump and molecular pump in sequence to make the vacuum degree in the microwave chamber reach 2×10 -4 After 0.05 ℃, H2 was introduced to generate a hydrogen-rich environment and ignition was carried out at the same time. After the glow in the chamber was stable for 5 minutes, the carbon source CH4 was introduced to start the growth of the heat dissipation diamond layer, and a certain flow of Ar was introduced to assist the growth; the microwave power was 2500 W, the growth temperature was 850 ℃, the pressure in the chamber was 80 Pa, and the atmosphere ratio was H2:CH4:Ar=20-24:2:1; after 5 hours of growth, Ar was introduced, and after the chamber returned to normal temperature and pressure, the temperature was slowly raised to 250 ℃ for 60 minutes of annealing to obtain a complete DLC / GaN / diamond sample.
[0013] As a further solution of the present invention: polishing the Si / DLC auxiliary layer specifically includes: S41, using chemical mechanical polishing equipment to remove the Si / DLC auxiliary layer from the prepared DLC / GaN / diamond sample, grinding using 800, 1500, 2000, 3000 and 5000 mesh mechanical grinding discs until the GaN layer is exposed and then polishing; S42. Polishing is performed using a polishing cloth and a polishing liquid. The polishing cloth is a Sat woven fabric polishing cloth. The polishing liquid formula is: 10 vol% Al2O3 and 90 vol% diamond. The particle size of Al2O3 is 300 nm, the particle size of diamond powder is 20 nm, and the polishing speed is 3500 r / min.
[0014] The beneficial effects of the present invention are: 1) The present invention first protects the surface of the Si-based GaN sample, grinds and polishes the Si substrate to 0.5 μm using a chemical mechanical polishing device, and then prepares a layer of DLC film on the Si surface at room temperature using a PECVD method, and then anneals the film to release stress while enhancing its mechanical strength, providing a stress release point for subsequent heteroepitaxial diamond. Due to the addition of a DLC film with high thermal conductivity and variable thermal expansion coefficient, the temperature and deformation stress of the sample can be effectively assisted in the subsequent MPCVD high-temperature growth of diamond. Compared with the traditional heteroepitaxial growth method of diamond, it is more stable, effectively reduces the failure caused by thermal stress deformation of diamond and GaN during the heteroepitaxial growth process, and improves the production capacity and yield of diamond and GaN modules. It has great application potential in the field of GaN / diamond integration; 2) The physical properties of the DLC used in the present invention can be changed by controlling the concentration of the carbon source (CH4) introduced during DLC deposition or the deposition power, that is, the thermal expansion coefficient of DLC can be changed by process parameters, so that it reaches an ideal value without introducing a new auxiliary layer. Secondly, DLC is easy to adhere. Compared with other auxiliary layers, it can be well deposited and attached to the Si substrate at room temperature, so as to prepare a layer of auxiliary layer with a similar thermal expansion coefficient and easy to deposit on the Si substrate. Then, the DLC auxiliary layer of GaN is placed downward on a high-temperature resistant graphite felt. When growing diamond at high temperature, due to the presence of a certain thermal gradient inside the sample, the heat diffuses from top to bottom to the DLC auxiliary layer with a certain heat dissipation capacity and thermal deformation capacity. At the same time, the DLC auxiliary layer is annealed to strengthen the interface bonding strength, so that the GaN that should be deformed during the high-temperature growth of diamond has mechanical support here, which greatly reduces the frequency of curling during the GaN heteroepitaxial diamond heat dissipation layer. Due to the introduction of the DLC auxiliary layer, when the thermal stress is too large, the DLC auxiliary layer can provide a stress release point, ensuring the yield of GaN / diamond. Finally, when the Si / DLC auxiliary layer is polished off, it will not have a significant impact on the GaN / diamond heat dissipation module. During this process, the tensile stress of GaN can be maintained at a good level without large deformation. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 A flow chart of the DLC-assisted stress-released GaN / diamond integration prepared by the present invention; Figure 2 A schematic diagram of a DLC auxiliary layer prepared in the present invention; Figure 3 Schematic diagram of the tensile testing method for the GaN / diamond module prepared in the present invention.
[0016] In the figure, 1. GaN layer; 2. Si substrate; 3. DLC auxiliary stress release layer; 4. AlN buffer layer; 5. Diamond heat dissipation layer. DETAILED DESCRIPTION
[0017] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] Embodiment 1, as Figure 1 As shown, a DLC-assisted stress release GaN / diamond integration method includes DLC-assisted stress release GaN / diamond, wherein the DLC-assisted stress release GaN / diamond is composed of a GaN layer 1, a Si substrate 2, a DLC-assisted stress release layer 3, an AlN buffer layer 4 and a diamond heat dissipation layer 5, wherein the GaN layer 1 is located above the Si substrate 2, the DLC-assisted stress release layer 3 is located below the Si substrate 2, the AlN buffer layer 4 is located above the GaN layer 1, and the diamond heat dissipation layer 5 is located above the AlN buffer layer 4; The integrated approach includes the following steps: S1. Sample pretreatment: the Si-based GaN sample is ultrasonically cleaned with a cleaning solution and then dried with an Ar air gun. The GaN surface is protected and the Si substrate is ground and polished using a chemical mechanical polishing device, leaving a certain thickness of Si layer for the deposition of the DLC auxiliary layer. S2, preparing a DLC auxiliary layer, using the treated Si-based GaN sample to prepare a DLC film on the Si substrate at room temperature using a plasma enhanced chemical vapor deposition (PECVD, Plasma Enhanced Chemical Vapor Deposition) method, and then annealing the film; S3. Prepare a GaN / diamond heat dissipation module, grow an AlN buffer layer on the GaN surface using the metal-organic chemical vapor deposition method (MOCVD), and then grow high-quality heat dissipation diamond using the microwave plasma chemical vapor deposition method (MPCVD) at high temperature; S4. Polish the Si / DLC auxiliary layer to obtain a complete GaN / diamond module.
[0019] Embodiment 2, as Figures 2 to 3As shown, a DLC-assisted stress-released GaN / diamond integration method, the thickness of GaN is 450 μm, and the integration method includes the following steps: Sample pretreatment: The surface of the Si-based GaN sample is cleaned and pretreated. The Si-based GaN sample is placed in a cleaning solution prepared by 70 vol% concentrated sulfuric acid and 30 vol% hydrogen peroxide. The sample is heated in a water bath under an ultrasonic cleaning device, and the temperature is raised from room temperature to 65°C at a rate of 5°C / min. After ultrasonic cleaning for 10 minutes, the sample is placed in deionized water for ultrasonic cleaning for 10 seconds and then taken out. The sample is blown dry with an Ar air gun and set aside. The GaN surface of the Si-based GaN sample is protected with a chip protection film. The Si substrate is polished by chemical mechanical polishing. Mechanical grinding discs of 800, 1500, 2000, 3000 and 5000 mesh are used for grinding. Polishing is performed until 0.5 μm of the Si substrate remains. The Si substrate is polished by polishing cloth and polishing liquid. The polishing cloth is a Sat woven fabric polishing cloth, and the polishing liquid formula is: the volume fraction is 40 vol% SiO2 and volume fraction of diamond is 60 vol%; the particle size of SiO2 is 150 nm, the particle size of diamond powder is 50 nm, and the polishing speed is 3500 r / min.
[0020] Prepare the DLC auxiliary layer, place the processed GaN sample Si side up, and place a layer of high-temperature resistant graphite felt at the bottom of the sample to prevent the chip protection film from burning or melting due to excessive temperature; place the sample in the PECVD sample chamber; the gas introduced during the preparation is 99.99% pure Ar, and the carbon source is 99.99% pure CH4; the flow rate of CH4 is 20sccm, the flow rate of Ar is 10sccm, the base temperature is room temperature 27°C, the internal total air pressure is 12Pa, the RF power is 175W, the sputtering current is 0.5A, and the deposition rate is 5nm / min; use a mechanical pump for preliminary vacuum extraction, and the pressure in the sample chamber reaches 4Pa after 30min; when the actual vacuum degree in the sample chamber reaches the preset pressure, use a molecular pump to extract high vacuum in the sample chamber until the vacuum degree in the sample chamber reaches 2×10 -3 Pa, and at the same time slowly heat the temperature in the sample chamber to maintain it at 45°C; use Ar plasma to clean and activate the Si surface for 110s; end the deposition after 4h, and refill Ar, wait for the sample chamber to return to normal temperature and pressure, take out the sample, clean it with deionized water, and obtain a 1200nm DLC auxiliary layer after Ar drying; place the Si-based GaN sample with the DLC auxiliary layer prepared in an atmosphere furnace, and anneal it at 200°C and N2 atmosphere for 60min.
[0021] Prepare the GaN / diamond heat dissipation module, place the GaN surface of the annealed sample upward and remove the chip protection film, and place the sample on the high-temperature resistant graphite felt in the MOCVD sample chamber; introduce NH3 as the N source and TMAl as the Al source, with flow rates of 25000sccm and 240sccm respectively, the growth temperature is 800℃, the power is 1500W, and the growth pressure is 3×10 4 Pa; after 150 minutes of deposition, Ar was refilled, and the sample chamber was restored to normal temperature and pressure. The sample with the AlN buffer layer deposited was taken out, and it was ultrasonically cleaned with anhydrous ethanol and deionized water for 10 minutes. After being blown dry with an Ar air gun, it was placed on the graphite felt in the microwave chamber of the MPCVD for the final growth of the heat dissipation diamond layer; the mechanical pump and molecular pump were used in turn to make the vacuum degree in the microwave chamber reach 2×10 -4 Pa, H2 was introduced to generate a hydrogen-rich environment and ignition was carried out at the same time. After the glow in the chamber was stable for 5 minutes, the carbon source CH4 was introduced to start the growth of the heat dissipation diamond layer, and a certain flow of Ar was introduced to assist the growth; the microwave power was 2500W, the growth temperature was 850℃, the pressure in the chamber was 80Pa, and the atmosphere ratio was H2:CH4:Ar=20:2:1; after 5h of growth, Ar was introduced, and after the chamber returned to normal temperature and pressure, the temperature was slowly raised to 250℃ for 60min of annealing to obtain a complete DLC / GaN / diamond sample.
[0022] Polish the Si / DLC auxiliary layer, use chemical mechanical polishing equipment to remove the Si / DLC auxiliary layer of the prepared DLC / GaN / diamond sample, use 800, 1500, 2000, 3000 and 5000 mesh mechanical grinding discs for grinding until the GaN layer is exposed; use polishing cloth and polishing liquid to polish, the polishing cloth is Sat woven fabric polishing cloth, and the polishing liquid formula is: 10 vol% Al2O3 and 90 vol% diamond; the particle size of Al2O3 is 300nm, the particle size of diamond powder is 20nm, and the polishing speed is 3500r / min.
[0023] The GaN / diamond module prepared in the above embodiment is subjected to a tensile stress test using a universal material testing machine. The test method is as follows: Figure 3 As shown: Labels were attached to both ends of the GaN / diamond module, and the two ends of the module were clamped using the fixture of a universal material testing machine, and tensile pressure was applied at a speed of 1 mm / s; the tensile stress test result was 0.41 GPa.
[0024] Embodiment three, as Figures 2 to 3 As shown, a DLC-assisted stress-released GaN / diamond integration method, the thickness of GaN is 450 μm, and the integration method includes the following steps: Sample pretreatment: The surface of the Si-based GaN sample is cleaned and pretreated. The Si-based GaN sample is placed in a cleaning solution prepared by 70 vol% concentrated sulfuric acid and 30 vol% hydrogen peroxide. The sample is heated in a water bath under an ultrasonic cleaning device, and the temperature is raised from room temperature to 65°C at a rate of 5°C / min. After ultrasonic cleaning for 10 minutes, the sample is placed in deionized water for ultrasonic cleaning for 10 seconds and then taken out. The sample is blown dry with an Ar air gun and set aside. The GaN surface of the Si-based GaN sample is protected with a chip protection film. The Si substrate is polished by chemical mechanical polishing. 800, 1500, 2000, 3000 and 5000 mesh mechanical grinding discs are used for grinding. Polishing is performed until 0.5 μm of the Si substrate remains. The Si substrate is polished by a polishing cloth and a polishing liquid. The polishing cloth is a Sat woven fabric polishing cloth, and the polishing liquid formula is: 40 vol% SiO2 and 60 vol% Diamond; the particle size of SiO2 is 150nm, the particle size of diamond powder is 50nm, and the polishing speed is 3500r / min.
[0025] Prepare the DLC auxiliary layer, place the processed GaN sample Si side up, and place a layer of high-temperature resistant graphite felt at the bottom of the sample to prevent the chip protection film from burning or melting due to excessive temperature; place the sample in the PECVD sample chamber; the gas introduced during the preparation is 99.99% pure Ar, and the carbon source is 99.99% pure CH4; the flow rate of CH4 is 20sccm, the flow rate of Ar is 10sccm, the base temperature is room temperature 27°C, the internal total air pressure is 10Pa, the RF power is 170W, the sputtering current is 0.6A, and the deposition rate is 5nm / min; use a mechanical pump for preliminary vacuum extraction, and the pressure in the sample chamber reaches 4Pa after 30min; when the actual vacuum degree in the sample chamber reaches the preset pressure, use a molecular pump to extract high vacuum in the sample chamber until the vacuum degree in the sample chamber reaches 2×10 -3 Pa, and at the same time slowly heat the temperature in the sample chamber to maintain it at 45°C; use Ar plasma to clean and activate the Si surface for 110s; end the deposition after 4h, and refill Ar, wait for the sample chamber to return to normal temperature and pressure, take out the sample, clean it with deionized water, and obtain a 1200nm DLC auxiliary layer after Ar drying; place the Si-based GaN sample with the DLC auxiliary layer prepared in an atmosphere furnace, and anneal it at 200°C and N2 atmosphere for 60min.
[0026] Prepare the GaN / diamond heat dissipation module, place the GaN surface of the annealed sample upward and remove the chip protection film, and place the sample on the high-temperature resistant graphite felt in the MOCVD sample chamber; introduce NH3 as the N source and TMAl as the Al source, with flow rates of 25000sccm and 240sccm respectively, the growth temperature is 800℃, the power is 1500W, and the growth pressure is 3×10 4 Pa; after 150 minutes of deposition, Ar was refilled, and the sample chamber was restored to normal temperature and pressure. The sample with the AlN buffer layer deposited was taken out, and it was ultrasonically cleaned with anhydrous ethanol and deionized water for 10 minutes. After being blown dry with an Ar air gun, it was placed on the graphite felt in the microwave chamber of the MPCVD for the final growth of the heat dissipation diamond layer; the mechanical pump and molecular pump were used in turn to make the vacuum degree in the microwave chamber reach 2×10 -4 Pa, H2 was introduced to generate a hydrogen-rich environment and ignition was carried out at the same time. After the glow in the chamber was stable for 5 minutes, the carbon source CH4 was introduced to start the growth of the heat dissipation diamond layer, and a certain flow of Ar was introduced to assist the growth; the microwave power was 2500W, the growth temperature was 850℃, the pressure in the chamber was 80Pa, and the atmosphere ratio was H2:CH4:Ar=24:2:1; after 5h of growth, Ar was introduced, and after the chamber returned to normal temperature and pressure, the temperature was slowly raised to 250℃ for 60min of annealing to obtain a complete DLC / GaN / diamond sample.
[0027] Polish the Si / DLC auxiliary layer, use chemical mechanical polishing equipment to remove the Si / DLC auxiliary layer of the prepared DLC / GaN / diamond sample, use 800, 1500, 2000, 3000 and 5000 mesh mechanical grinding discs for grinding until the GaN layer is exposed; use polishing cloth and polishing liquid to polish, the polishing cloth is Sat woven fabric polishing cloth, and the polishing liquid formula is: 10 vol% Al2O3 and 90 vol% diamond; the particle size of Al2O3 is 300nm, the particle size of diamond powder is 20nm, and the polishing speed is 3500r / min.
[0028] The GaN / diamond module prepared in the above embodiment is subjected to a tensile stress test using a universal material testing machine. The test method is as follows: Figure 3 As shown: Labels were attached to both ends of the GaN / diamond module, and the two ends of the module were clamped using the fixture of a universal material testing machine, and tensile pressure was applied at a speed of 1 mm / s; the tensile stress test result was 0.48 GPa.
[0029] The Si-based GaN sample is ultrasonically cleaned with a cleaning solution and then blown dry with an Ar air gun, and the GaN layer 1 is protected. The Si substrate 2 is ground and polished using a chemical mechanical polishing device, and a DLC film is prepared on the Si surface at room temperature using PECVD. The DLC film is then annealed to form a DLC auxiliary stress release layer 3. An AlN buffer layer 4 is prepared on the treated GaN surface of the sample using MOCVD, and then a diamond heat dissipation layer 5 is epitaxially grown using MPCVD.
[0030] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
[0031] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A DLC-assisted stress-released GaN / diamond integration method, comprising DLC-assisted stress-released GaN / diamond, characterized in that: The DLC-assisted stress-release GaN / diamond is composed of a GaN layer (1), a Si substrate (2), a DLC-assisted stress-release layer (3), an AlN buffer layer (4) and a diamond heat dissipation layer (5); the GaN layer (1) is located above the Si substrate (2), the DLC-assisted stress-release layer (3) is located below the Si substrate (2), the AlN buffer layer (4) is located above the GaN layer (1), and the diamond heat dissipation layer (5) is located above the AlN buffer layer (4); The integration method comprises the following steps: S1. Sample pretreatment: After the Si-based GaN sample is ultrasonically cleaned with a cleaning solution, it is blown dry with an Ar air gun, and the GaN surface is protected. The Si substrate is ground and polished using a chemical mechanical polishing device, and the Si layer is retained for the deposition of the DLC auxiliary layer; S2, preparing a DLC auxiliary layer, using an ion enhanced chemical vapor deposition method to deposit a DLC film on a Si substrate at room temperature, and then annealing the DLC film; S3, preparing a GaN / diamond heat dissipation module, using a metal organic chemical vapor deposition method to grow an AlN buffer layer on the GaN surface, and then using a microwave plasma chemical vapor deposition method to grow high-quality heat dissipation diamond in a high-temperature growth manner; S4. Polish the Si / DLC auxiliary layer to obtain a complete GaN / diamond module.
2. The integration method according to claim 1, characterized in that: In S1, sample pretreatment specifically includes: S11, performing cleaning pretreatment on the surface of the Si-based GaN sample, placing the Si-based GaN sample in a cleaning solution prepared by 70 vol% concentrated sulfuric acid and 30 vol% hydrogen peroxide, heating it in a water bath under an ultrasonic cleaning device, raising the temperature to 65°C at a rate of 5°C / min, ultrasonically cleaning it for 10 minutes, placing it in deionized water for ultrasonic cleaning for 10 seconds, and then taking it out; S12, using an Ar air gun to blow dry and set aside, protecting the GaN surface of the Si-based GaN sample with a chip protection film, grinding the Si substrate using a chemical mechanical polishing method, using 800, 1500, 2000, 3000 and 5000 mesh mechanical grinding discs, until 0.5 μm of the Si substrate remains and then polishing is performed; S13. The Si substrate is ground and polished using a polishing cloth and a polishing liquid. The polishing cloth is a Sat woven fabric polishing cloth, and the polishing liquid formula is: 40 vol% SiO2 and 60 vol% diamond; the particle size of SiO2 is 150 nm, the particle size of diamond powder is 50 nm, and the polishing speed is 3500 r / min.
3. The integration method according to claim 1, characterized in that: In S2, preparing the DLC auxiliary layer specifically includes: S21. Place the processed GaN sample Si side upwards, and place a layer of high-temperature resistant graphite felt at the bottom of the sample to prevent the chip protection film from burning or melting due to excessive temperature. Place the sample in the PECVD sample chamber. The gas introduced during the preparation is 99.99% pure Ar, and the carbon source is 99.99% pure CH4; the flow rate of CH4 is 20sccm, the flow rate of Ar is 10sccm, the base temperature is 27°C, the internal total pressure is 10-12Pa, the RF power is 170-175W, the sputtering current is 0.5-0.6A, and the deposition rate is 5nm / min; S22. Use a mechanical pump to perform preliminary vacuum extraction. After 30 minutes, the pressure in the sample chamber reaches a high vacuum degree. Extraction is performed until the vacuum degree in the sample chamber reaches 2×10 -3 Pa, and at the same time slowly heat the temperature in the sample chamber to maintain it at 45°C; S23, using Ar plasma to clean and activate the Si surface for 110 seconds; S24, the deposition is terminated after 4 hours, and Ar is refilled, and the sample chamber is waited to return to normal temperature and pressure, and the sample is taken out and washed with deionized water, and dried with Ar to obtain a 1200nm DLC auxiliary layer; S25. Place the Si-based GaN sample with the DLC auxiliary layer prepared in an atmosphere furnace and anneal it at 200° C. in a N2 atmosphere for 60 minutes.
4. The integration method according to claim 1, characterized in that: In S3, preparing the GaN / diamond heat dissipation module specifically includes: S31, facing the GaN surface of the annealed sample upwards, removing the chip protection film, and placing the sample on a high temperature resistant graphite felt in the MOCVD sample chamber; S32, NH3 as N source, TMAl as Al source, flow rates of 25000sccm and 240sccm respectively, growth temperature of 800℃, power of 1500W, growth pressure of 3×10 4 Pa, after 150 minutes of deposition, Ar is backfilled, and when the sample chamber returns to normal temperature and pressure, the sample with the AlN buffer layer deposited is taken out, and it is ultrasonically cleaned with anhydrous ethanol and deionized water for 10 minutes, and blown dry with an Ar air gun, and then placed on the graphite felt in the microwave chamber of the MPCVD for the final growth of the heat dissipation diamond layer; S33, use mechanical pump and molecular pump in turn to make the vacuum degree in the microwave chamber reach 2×10 -4 Pa, H2 was introduced to generate a hydrogen-rich environment and ignition was carried out at the same time. After the glow in the chamber was stable for 5 minutes, the carbon source CH4 was introduced to start the growth of the heat dissipation diamond layer, and Ar was filled in for auxiliary growth. The microwave power was 2500W, the growth temperature was 850℃, the pressure in the chamber was 80Pa, and the atmosphere ratio was H2:CH4:Ar=20-24:2:
1. After 5 hours of growth, Ar was introduced. After the chamber returned to normal temperature and pressure, the temperature was slowly raised to 250℃ and annealing treatment was carried out for 60 minutes to obtain a complete DLC / GaN / diamond sample.
5. The integration method according to claim 1, characterized in that: In S4, polishing the Si / DLC auxiliary layer specifically includes: S41, using chemical mechanical polishing equipment to remove the Si / DLC auxiliary layer from the prepared DLC / GaN / diamond sample, grinding using 800, 1500, 2000, 3000 and 5000 mesh mechanical grinding discs until the GaN layer is exposed and then polishing; S42. Polishing is performed using a polishing cloth and a polishing liquid. The polishing cloth is a Sat woven fabric polishing cloth. The polishing liquid formula is: 10 vol% Al2O3 and 90 vol% diamond. The particle size of Al2O3 is 300 nm, the particle size of diamond powder is 20 nm, and the polishing speed is 3500 r / min.
Citation Information
Patent Citations
Method of integrating diamond and gallium nitride
CN110838438A
Preparation method of GaN / diamond film composite sheet
CN104328390A
Heat resistant diamond-like thin film, machine part provided therewith, die, and its production method
JP2007308753A
Systems and Methods for Fabricating Single-Crystalline Diamond Membranes
US20170352538A1
Crystalline Semiconductor Growth on Amorphous and Poly-Crystalline Substrates
US20180158672A1